Physical activity and FTO genotype by physical activity interactive influences on obesity. Issue 1 (December 2016) - Kim, Joon; DeMenna, Jacob; Puppala, Sobha; Chittoor, Geetha; Schneider, Jennifer; Duggirala, Ravindranath; Mandarino, Lawrence; Shaibi, Gabriel; Coletta, Dawn
Abstract Background Although the effect of the fat mass and obesity-associated (FTO) gene on adiposity is well established, there is a lack of evidence whether physical activity (PA) modifies the effect of FTO variants on obesity in Latino populations. Therefore, the purpose of this study was to examine PA influences and interactive effects between FTO variants and PA on measures of adiposity in Latinos. Results After controlling for age and sex, participants who did not engage in regular PA exhibited higher BMI, fat mass, HC, and WC with statistical significance (P  < 0.001). Although significant associations between the three FTO genotypes and adiposity measures were found, none of the FTO genotype by PA interaction assessments revealed nominally significant associations. However, several of such interactive influences exhibited considerable trend towards association. Conclusions These data suggest that adiposity measures are associated with PA and FTO variants in Latinos, but the impact of their interactive influences on these obesity measures appear to be minimal. Future studies with large sample sizes may help to determine whether individuals with specific FTO variants exhibit differential responses to PA interventions.